2001
DOI: 10.1002/ps.298
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cytochrome P‐450 enzyme activity in the selectivity and safening action of pyrazosulfuron‐ethyl

Abstract: To investigate the selectivity and safening action of the sulfonylurea herbicide pyrazosulfuron-ethyl (PSE), pyrazosulfuron-ethyl O-demethylase (PSEOD) activity involving oxidative metabolism by cytochrome P-450 was studied in rice (Oryza sativa L cv Nipponbare) and Cyperus serotinus Rottb. Cytochrome P-450-dependent activity was demonstrated by the use of the inducers 1,8-naphthalic anhydride and ethanol, the herbicides PSE, bensulfuron-methyl, dimepiperate and dymron, or the inhibitor piperonyl butoxide (PBO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In addition to the compounds listed in Table 1, P450s have been implicated in the metabolism of several herbicides by in vivo studies in which the changes in herbicidal activity and/or the rate of herbicide metabolism were measured in response to various P450 inhibitors. Unconfirmed by in vitro data, the involvement of P450s are suggested by in vivo results in the metabolism of chlortoluron in wheat (Canivenc et al 1989;Mougin et al 1992), corn and cotton (Cole and Owen 1987); bentazon in soybean (Sterling and Balke 1990); pyrazosulfuron ethyl in rice (Yun et al 2001); clodinafop in wheat, barley and corn (Kreuz et al 1991); phenoxaprop-p-ethyl in barley (Romano et al 1993); clomazone in cotton (Ferhatoglu et al 2005); thiazopyr in several weedy species (Feng et al 1995) and EPTC in some cereals (Barta and Dutka 1991). (Additional examples are discussed under ''P450-Endowed Herbicide Resistance in Weeds'').…”
Section: Several Herbicides Are Metabolized By P450s In Plantsmentioning
confidence: 78%
“…In addition to the compounds listed in Table 1, P450s have been implicated in the metabolism of several herbicides by in vivo studies in which the changes in herbicidal activity and/or the rate of herbicide metabolism were measured in response to various P450 inhibitors. Unconfirmed by in vitro data, the involvement of P450s are suggested by in vivo results in the metabolism of chlortoluron in wheat (Canivenc et al 1989;Mougin et al 1992), corn and cotton (Cole and Owen 1987); bentazon in soybean (Sterling and Balke 1990); pyrazosulfuron ethyl in rice (Yun et al 2001); clodinafop in wheat, barley and corn (Kreuz et al 1991); phenoxaprop-p-ethyl in barley (Romano et al 1993); clomazone in cotton (Ferhatoglu et al 2005); thiazopyr in several weedy species (Feng et al 1995) and EPTC in some cereals (Barta and Dutka 1991). (Additional examples are discussed under ''P450-Endowed Herbicide Resistance in Weeds'').…”
Section: Several Herbicides Are Metabolized By P450s In Plantsmentioning
confidence: 78%
“…Previous research has found that cloquintocet-mexyl antagonized the effects of malathion or ABT on topramezone, but the implications of this are not clear. It is possible that cloquintocet-mexyl increased topramezone metabolism through mechanisms not catalyzed by P450 monooxygenases [39,40]. We speculated that isoxadifen-ethyl increased plant metabolism of nicosulfuron through non-P450-catalyzed routes or through P450 monooxygenases not inhibited by PBO, ABT, and malathion.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that isoxadifen-ethyl increased plant metabolism of nicosulfuron through non-P450-catalyzed routes or through P450 monooxygenases not inhibited by PBO, ABT, and malathion. Yun et al [40] evaluated the effects of the P450 monoxygenase inhibitor PBO alone and in combination with safeners on the activity of microsomal pyrazosulfuron-ethyl O-demethylase, which metabolizes pyrazosulfuron-ethyl in rice ( Oryza sativa L.). They found that PBO inhibited 63% of pyrazosulfuron-ethyl O-demethylase activity when applied in combination with the herbicide, but only 19% inhibition was achieved when PBO was applied in combination with the herbicide and the safener.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivity of some plants to clomazone may also be related to the action site of the cytochrome P-450 mono-oxygenase enzyme, which is involved in resistance metabolites of various herbicides (Yun et al, 2001). This enzyme normally acts with the function of detoxifying, and it may responsible for the oxidation of the clomazone molecule, making it more toxic to plants (Yun et al, 2005).…”
Section: Resultsmentioning
confidence: 99%